Risk Factors for Hypoglycaemia in Acute Gastroenteritis in Children Under Five Years of Age - Abbas, Arooj; Urooj, Saba; Abbas, Sikandar; Abbas, Taimoor; Abbas, Hira; Iftikhar, Umer (Biological and Clinical Sciences Research Journal, 2025)
Acute gastroenteritis (AGE) in children is one of the leading health problems, especially in developing countries. Objective: To find the frequency of hypoglycemia in Acute Gastroenteritis in children under five years of age. Methods: This Descriptive case series was conducted at the Pediatrics Medical Emergency Department, Children Hospital, and the University of Child Health Sciences Lahore from November 2024 till May 2025. Data were collected through a Non-probability consecutive sampling technique. Results: Data were collected from 200 patients. The results show no significant difference in mean age, gender distribution, or sex proportions between cases and controls, as indicated by p-values >0.05. However, mean weight was significantly lower in cases (12.4 ± 2.1 kg) compared to controls (13.5 ± 2.0 kg), with a p-value <0.05. Additionally, mean blood glucose levels were significantly lower in cases (48.3 ± 7.5 mg/dL) than in controls (85.7 ± 12.4 mg/dL), with a highly significant p-value <0.001. No dehydration was observed in only 5% of cases compared to 25% of controls, with a p-value <0.01. Severe dehydration was significantly higher in cases (30%) than in controls (10%), with a highly significant p-value <0.001. Conclusion: It is concluded that severe dehydration and severe malnourishment are important risk factors associated with the condition under study.